Territorial Disparities and Health Inequities in Morocco - Abdesslam Boutayeb (Territorial Disparities and Health Inequities in Morocco, 2022)
Despite the implementation of several initiatives and action plans, aiming directly or indirectly at reducing inequalities in Morocco, territorial disparities and health inequities persistent and remain a crucial challenge for governments and policymakers. Morocco is engaged to achieve the 17 Sustainable Development Goals (SDG) and in particular SDG3 which aims to “Ensure healthy lives and promote well-being for all at all ages” by leaving no one behind. In this direction, the country is moving toward universal health coverage (UHC) with the ambition to cover the majority of its population. However, action on social determinants of health to reduce health iniquities remains a crucial challenge. A recent study showed that 23 out off 40 health indicators are associated with severe health iniquity and the Health Information System (HIS) in Morocco is still under construction. The first chapter of this book analyses the health information system in Morocco while the remaining three chapters deal with different aspects of health inequities in Morocco, illustrating the huge gaps and large disparities seen in terms of milieu of residence (rural-urban), wealth quintiles, education level and geographic regions. Comparison is based on vital health indicators like maternal mortality ratio (MMR), infant mortality rate (IMR), nutrition status, illiteracy, people in situation of disability, adolescent pregnancy and childbearing and others.